Glocal integrity in 420 stainless steel by asynchronous laser processing. Issue 1 (2019) - Sealy, M.P.; Hadidi, H.; Kanger, C.J.; Yan, X.L.; Cui, B.; McGeough, J.A.
Abstract: Cold working individual layers during additive manufacturing (AM) by mechanical surface treatments, such as peening, effectively "prints" an aggregate surface integrity that is referred to as a glocal (i.e., local with global implications) integrity. Printing a complex, pre-designed glocal integrity throughout the build volume is a feasible approach to improve functional performance while mitigating distortion. However, coupling peening with AM introduces new manufacturing challenges, namely thermal cancellation, whereby heat relaxes favorable residual stresses and work hardening when printing on a peened layer. Thus, this work investigates glocal integrity formation from cyclically coupling LENS® with laser peening on 420 stainless steel.